Southern African Pentecostal discourse and the construction of a new spiritual order: the case of a shift in the "World of Life International Ministries Discourse" about God - Manyawu, Andrew T. (LWATI, 2016)
This discussion reveals and examines the intense dynamism of a highly unstable social practice in Southern Africa – the Modern African Pentecostal Movement (MAP) – as reflected in the discursive practice of a key actor, a Word of Life International Ministries (WoLIM) Senior Pastor, M.B. Shana. One of her prayer texts is examined from a perspective of Critical Discourse Analysis (CDA). It is shown that, much as WoLIM teach strict adherence to Biblical text (Maxwell, 2006; Togarasei, 2007), Shana’s text represents a milestone in the evolution of the definition of the Christian divinity from a cult of a Trinity dominated by God the Father to a virtually exclusive relationship of believers with the Holy Spirit. The latter appears to be gradually assuming the superior rank of the Father and playing more roles than the Father and the Son together. This is achieved through an infusion of new semantic values into the concept of the Holy Spirit while the semantic values of the other two persons of the Trinity are diminished. This infusion is not only aided but also prompted by the Southern African context in which WoLIM operates.